1994
DOI: 10.1126/science.8153634
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Cycle Regulator Potentially Involved in Genesis of Many Tumor Types

Abstract: A putative tumor suppressor locus on the short arm of human chromosome 9 has been localized to a region of less than 40 kilobases by means of homozygous deletions in melanoma cell lines. This region contained a gene, Multiple Tumor Suppressor 1 (MTS1), that encodes a previously identified inhibitor (p16) of cyclin-dependent kinase 4. MTS1 was homozygously deleted at high frequency in cell lines derived from tumors of lung, breast, brain, bone, skin, bladder, kidney, ovary, and lymphocyte. Melanoma cell lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
1,449
1
23

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,521 publications
(1,500 citation statements)
references
References 15 publications
27
1,449
1
23
Order By: Relevance
“…These alterations include mutations of the TP53 genes (Mashiyama et al, 1991), homozygous deletion of the INK4A/MTS1 and INK4B/MTS2 genes (Kamb et al, 1994), inactivation of the PTEN1 gene Steck et al, 1997), ampli®cation of the EGFR, MDM2, PDGFR, CDK4 and/or cyclin D3 genes (He et al, 1994;Hunter et al, 1995;Kumabe et al, 1992;Sonoda et al, 1995b;Kuchiki et al, 2000) as well as frequent loss of chromosomal loci on 9p, 10, 11q, 13q, 17p, 19q, and 22q (Fults et al, 1990;Collins and James, 1993;Lang et al, 1994;Sonoda et al, 1995aSonoda et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations include mutations of the TP53 genes (Mashiyama et al, 1991), homozygous deletion of the INK4A/MTS1 and INK4B/MTS2 genes (Kamb et al, 1994), inactivation of the PTEN1 gene Steck et al, 1997), ampli®cation of the EGFR, MDM2, PDGFR, CDK4 and/or cyclin D3 genes (He et al, 1994;Hunter et al, 1995;Kumabe et al, 1992;Sonoda et al, 1995b;Kuchiki et al, 2000) as well as frequent loss of chromosomal loci on 9p, 10, 11q, 13q, 17p, 19q, and 22q (Fults et al, 1990;Collins and James, 1993;Lang et al, 1994;Sonoda et al, 1995aSonoda et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The p16 INK4a and p15 INK4b genes, which lie very close in the human and murine chromosomes (Kamb et al, 1994;Quelle et al, 1995), are frequently deleted in a wide range of tumors Hirama and Koe er, 1995). Deletions most frequently involve both p16 INK4a and p15 INK4b .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that deletion of the p16INK4 gene is common in various human tumors [4], and the encoded protein has been identified as a regulatory product in the cell cycle. p16INK4 inhibits the CDK4-cyclin D complexes, preventing the phosphorylation of regulatory proteins which block G1 to S transition and cell growth [5].…”
Section: Introductionmentioning
confidence: 99%